B‐lines beyond the thoracic cavity ‐ ultrasound identification of intercostal pulmonary hernia. Issue 1 (12th July 2021) - Gordon, Richard; Karfunkle, Benjamin; Smith, Hannah; Larimore, Katheryn; Turgiss, Krystal; Najeemuddin, Syed
Abstract: Intercostal pulmonary hernia is a rare condition that may present to the emergency department spontaneously, following blunt trauma or as a complication of thoracic surgery. With the evolution of minimally invasive thoracic surgery pulmonary hernia may become more common. In this case of postoperative chest pain, incisional swelling, and shortness of breath, we present the ultrasound characteristics of a postoperative intercostal pulmonary hernia and its resemblance to subcutaneous emphysema. Abstract : Axial (A) and sagittal (B) thoracic CT, optimized for lung parenchyma, demonstrating the intercostal pulmonary hernia and right pleural effusion